Profesionalitas Promosi Jabatan dalam Peningkatan Kinerja Pelayanan Publik pada Dinas Pekerjaan Umum dan Perumahan Rakyat Provinsi Papua Barat - Momot, Yohanis; Silo, Akbar; Ohoiwutun, Yosephina; Muhdiarta, Untung (Program Doktor Ilmu Sosial Universitas Cenderawasih, 2023)
This study aims to reveal a professional description of promotion, supporting slot maxwin factors, and inhibiting factors, and a strategy for a promotion system that is in accordance with the work professionalism of the Public Works and Public Housing Office of West Papua Province can produce public service performance. The research approach used is a mixed method that combines a qualitative research approach, to see the depth of data through interviews and field observations, then a quantitative approach using statistical benchmarks or regression using survey methods. Qualitative data analysis includes the stages of data reduction, data presentation, and verification, and drawing conclusions. While the quantitative analysis is through the Kolmogorov-Smirnov normality test. The research results show that the mechanism is not yet transparent. Supporting factors and inhibiting factors that influence the professionalism of promotion are closely related to its internal and external dimensions. If the supporting factors cannot be optimized and the inhibiting factors cannot be handled properly, then promotion cannot be carried out professionally. Public Service Standards and Reputation can be described by the degree of achievement by examining the consistent aspects of achieving the goals supported by the presentation of the Public Service Index